Endothelium-dependent vasodilation in myogenically active mouse skeletal muscle arterioles: role of EDH and K(+) channels. - Potocnik, S; McSherry, I; Ding, H; Murphy, T; Kotecha, N; Dora, K; Yuill, K; Triggle, C; Hill, M (2009)
As smooth muscle cell (SMC) membrane potential (E(m)) is critical for vascular responsiveness, and arteriolar SMCs are depolarized at physiological intraluminal pressures, we hypothesized that myogenic tone impacts on dilation mediated by endothelium-derived hyperpolarization (EDH). Studies were performed on cannulated mouse cremaster arterioles [diameter, 33+/-2 microm (n=23) at 60 mmHg; SMC Em -34.6+/-1.2 mV (n=7)]. Myogenic activity was assessed as tone developed in response to intraluminal pressure. Functional observations were related to mRNA, protein expression, and anatomy. Acetylcholine concentration-response curves showed a modest shift following indomethacin (10 microM) and L-NAME (100 microM), although maximal vasodilation was achieved. Residual dilation was removed by apamin (1 microM) in combination with TRAM-34 (1 microM) or charybotoxin (0.1 microM), indicating the requirement of small (S) and intermediate (I) calcium-activated potassium channels (K(Ca)). Charybdotoxin, but not TRAM-34, caused vasoconstriction, presumably through the inhibition of SMC BK(Ca). Expression of SK3 and IK1 was confirmed by immunohistochemistry and polymerase chain reaction, while myoendothelial junctions were common, suggesting a high degree of cell coupling. Also consistent with a role for endothelial K(Ca) channels, acetylcholine increased endothelium [Ca(2 +)](i). Apamin and TRAM-34 similarly blocked EDH-mediated dilation at intraluminal pressures of 30 and 90 mmHg, suggesting that in mouse arterioles, SK(Ca -) and IK(Ca -) mediated mechanisms predominate and operate independently of physiological levels of myogenic activation.